THE EFFECT OF VIDEO MEDIA ON STUDENTS’ PUBLIC SPEAKING SKILLS FOR NURSING STUDENTS - cahyadi wiharjo (Journal of Language Education (JoLE), 2025)
This study investigates the effectiveness of using video media to improve students’ skills for public speaking. Employing a mixed-method approach, the research involved 50 second-year nursing students from Universitas YPIB Majalengka, selected through purposive sampling. Quantitative data were obtained using pre-test and post-test assessments to evaluate students’ speaking performance before and after the video-based intervention. Additionally, qualitative data were obtained through a close-ended questionnaire to explore students’ perceptions of using videos as a learning tool. The results of the paired t-test analysis showed a statistically significant improvement in students’ public speaking abilities, with the t-observed value (2.24) exceeding the t-critical value (2.015). Furthermore, the questionnaire responses indicated that approximately 80% of the participants responded positively to the use of videos, reporting increased motivation, confidence, and engagement. These findings suggest that video media, particularly authentic and inspirational video talks, can be an effective tool for developing public speaking skills among students. The study concludes with recommendations for institutions, teachers, and future researchers to further support and explore the integration of video-based instruction in language learning